Aplikasi Konsep Black and Grey pada Brand Galeri Kent Tattoo studio di Surabaya - Wibowo, Cindy Yesika (Intra, 2013)
Nowadays, tattoos have been growing rapidly in Indonesia, especially Surabaya. But there are still a lot of stigma and the negative will be the art of the tattoo itself by the people of Surabaya. People assume tattoo art is taboo and tends to smell a criminal. The concept of Black and Grey selected because it has a much different meaning from a negative image to the tattoo. This concept is taken from the first tattoo in the world is Black and Grey. This concept is different from the concept of Kent Gallery Tattoo studio and give the impression of a creepy gothic. Expected with the application of Black and Grey Tattoo studio at Kent Gallery in Surabaya can change peoples negative views of tattoo art.